(untitled) (Journal of Engineering, 2025)
There is a continuous demand in geotechnical engineering to find more economical footing. Screw piles provide acceptable or even much more bearing against tensile, compression, lateral, and overturning moment loads with less impact on the environment and surrounding buildings. Screw piles may be utilized either as shallow footing or deep footing, and can be installed in various types of soils except the soils that contain gravel or stiff clay. A screw pile is generally made of high-quality steel shaft with a single helix plate or multiple helixes plates attached to the lower end of the shaft at specified spacing utilized by the designer. The current study highlighted the various theoretical and field methods that were utilized in literature to estimate the uplift capacity of screw piles and pointed out several field, laboratory scale, and numerical simulation studies that investigated the most important parameters during installation and uplift loading of the screw piles. The former investigations revealed that installing the screw piles with torque rotation speed ( ) of 1 (p/r) provides higher uplift capacities as well as increasing the embedment depth, the helix diameter, and the number of helical plates welded to the screw pile shaft. In general, the the decrease in the spacing ratio (S/D) gave higher uplift capacity in almost all the soils used by researchers this case can also be said to the decrease in the (L/D) ratio. Finally, increasing the undrained shear strength of clayey soil and the relative density of sandy soil gave a higher uplift capacity.